Efforts to Improve Students' Conceptual Understanding Ability in Islamic Education Learning with the Singing Method at SMP Negeri 2 Mapat Tunggal Selatan - Aslamiya (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve students' understanding ability in Islamic education learning by using the singing method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data of this study were obtained by test and observation techniques. The test is used to measure the increase in students' understanding ability in Islamic education learning and observation is used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the singing method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of completeness of improving students' understanding ability in each cycle with details of the pre-cycle 45.56%, the first cycle 66.47% and in the second cycle it increased to 89.57%. Thus, the use of singing method can be used as an alternative to increase student activity in Islamic education learning in Islamic religious education learning.